Protection of foreign investment in the Asia-Pacific co-operation region. - SORNARAJAH, M. (1995)
Examines the nature of the existing protection for foreign investment within the region, and explores avenues for moving towards a sounder system of investment protection. Looks at the ASEAN Investment Treaty, the only existing regional treaty, and the prospects for it serving as a model for a wider regional treaty. Analyses the principles in the APEC investment guidelines.